PERANCANGAN MESIN PENEPUNG DAUN LAMTORO DENGAN MENGGUNAKAN METODE VDI 2222 - Gama, Ronaldo Luis; Bale, Jefri; Tobe, Adi Y. (Universitas Nusa Cendana, 2023)
The method used in this research is the VDI 2222 method. The process of testing the tool is carried out by turning on the motor, and inputting the lamtoro leaves which will be floured into the tube, the results of the design of the lamtoro leaf powder machine with the VDI 2222 method and the results of the lamtoro leaf flour powder machine test, concluded as follows: Design of a lamtoro leaf crushing machine with engine dimensions, namely: Height 50 cm, Width 30 cm and Length 37 cm, and motor power ¼ hp and uses a belt and pulley transmission, by testing the weight of lamtoro leaves, namely 3000 gr (3 kg) with the required time of 420 minutes, then the flouring process is carried out so that it will produce lamtoro flour with a fineness level of 80 mesh. The design stages using the VDI 2222 method are carried out sequentially which can be adjusted to the needs.